2011
DOI: 10.1007/s10875-011-9606-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Function in Patients with Hereditary Angioedema: Elevated Soluble E-selectin Level During Inter-attack Periods

Abstract: These results demonstrate that in hereditary angioedema, the majority of endothelial functions are normal during inter-attack periods; however, soluble E-selectin levels are elevated. The higher soluble E-selectin plasma concentration is unlikely to result from inflammation; rather, it reflects enhanced shedding mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…That is, blood pressure, and the incidence of any vascular disease are not different between C1-INH-HAE and non-C1-INH-HAE populations, as indicated by data from this study, and from our previous studies [23,24]. Moreover, the similarities between the ET-1 levels of C1-INH-HAE patients and of controls are in agreement with our previous findings, which did not show any difference in ET-1 levels in smaller study cohorts [12]. The positive correlation between ADM level and age, or BMI [13,[25][26][27] and the gender difference in AVP level [14,28] are all well-known from other studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…That is, blood pressure, and the incidence of any vascular disease are not different between C1-INH-HAE and non-C1-INH-HAE populations, as indicated by data from this study, and from our previous studies [23,24]. Moreover, the similarities between the ET-1 levels of C1-INH-HAE patients and of controls are in agreement with our previous findings, which did not show any difference in ET-1 levels in smaller study cohorts [12]. The positive correlation between ADM level and age, or BMI [13,[25][26][27] and the gender difference in AVP level [14,28] are all well-known from other studies.…”
Section: Discussionsupporting
confidence: 92%
“…One hundred consecutive C1-INH-HAE patients were enrolled into the first part of this study (an enlarged patients population compared with that of our previous study [12]), who presented for their annual check-up at our Centre. Forty-two patients received danazol regularly (mean daily dose of danazol: 99 mg/day [range: 30-260 mg/day], mean duration of treatment: 11.8 [range 1-26 year]).…”
Section: C1-inh-hae Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, specific attention was paid to the possibility that an upregulation of different vasoactive substances may influence the risk of angioedema in C1-INH-HAE patients. E selectin, VGEF A and C and angiopoietin 2 are increased in these patients during intercritical periods and seem to predispose them to attacks [ 40 42 ]. Studying plasma markers of endothelial cells during angioedema attacks, Kajdacsi and colleagues found an activated phenotype suggesting that these cells actively participate in angioedema formation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the role of the endothelial cell in HAE attacks has received significant attention in recent years [5]. Czúcz et al [6] studied the endothelial cell functions of HAE patients during attack-free periods and compared those with that of healthy control subjects by monitoring 4 specific and sensitive plasma biomarkers of endothelial cells, i.e., soluble E-selectin, endothelin-1, von Willebrand factor (vWF) antigen, and vWF collagen-binding activity. They found that the majority of endothelial functions were normal during attack-free periods, although soluble E-selectin levels were elevated.…”
Section: Introductionmentioning
confidence: 99%